Implementation of the MIT KKN Program Group 56 Caruban Village in Improving Economic Empowerment, Education, and the Social Environment of the Community - Ghufron Nur Hasan; Aqil Luthfan (Prosiding Seminar Nasional Manajemen dan Ekonomi, 2024)
Community Service (KKN) activities are a form of community service carried out by students as part of the tridharma of higher education. This article describes the KKN activities carried out by the KKN team of the State Islamic University (UIN) Walisongo Semarang in Caruban Village, Ringinarum District, Kendal. The focus of this service is to improve the quality of education and health of the village community, as well as increasing the potential of Caruban Village. The results of the activities show an increase in the knowledge and skills of residents in the fields of education and health, as well as the creation of several sustainable programs to utilize the potential of the village initiated by the KKN team.